2019
DOI: 10.1101/563676
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pan-cancer mutational landscape of the PPAR pathway reveals universal patterns of dysregulated metabolism and interactions with tumor immunity and hypoxia

Abstract: Peroxisome proliferator-activated receptors (PPARs) are a family of nuclear receptors that regulate lipid metabolism and bioenergetic demands within living systems. Consequently, aberrant expression of PPAR genes could predispose individuals to diseases including cancer. PPAR signaling exerts pleiotropic functions in cancer, yet, little is known about the interactions between genetic and transcriptional events of pathway genes in a pan-cancer context. Employing multidimensional datasets of over 18,000 patients… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 61 publications
(53 reference statements)
2
13
0
Order By: Relevance
“…Cancer abbreviations were listed in Table S2 signalling were characterised by molecular footprints of stemness and that there was significant crosstalk between Notch-Hedgehog and other pathways involved in controlling tumour initiation. 28,29 Additionally, Gene Ontology analyses revealed significant enrichments of processes related to cell differentiation, cell proliferation, embryo development and morphogenesis ( Fig. 3d), supporting the hypothesis that tumour aggression and elevated mortality could be caused by the presence of CSCs that are likely to be refractory to therapy.…”
Section: Recurrently Amplified Driver Genes Associated With Notch Andsupporting
confidence: 61%
“…Cancer abbreviations were listed in Table S2 signalling were characterised by molecular footprints of stemness and that there was significant crosstalk between Notch-Hedgehog and other pathways involved in controlling tumour initiation. 28,29 Additionally, Gene Ontology analyses revealed significant enrichments of processes related to cell differentiation, cell proliferation, embryo development and morphogenesis ( Fig. 3d), supporting the hypothesis that tumour aggression and elevated mortality could be caused by the presence of CSCs that are likely to be refractory to therapy.…”
Section: Recurrently Amplified Driver Genes Associated With Notch Andsupporting
confidence: 61%
“…PPARs are involved in the regulation of metabolic homeostasis, whose activity are controlled by fatty acid ligands 34 . After activation, PPARs heterodimerize with retinoid X receptors (RXRs) to affect the expression of www.nature.com/scientificreports www.nature.com/scientificreports/ downstream genes.…”
Section: Discussionmentioning
confidence: 99%
“…The GO analysis unveiled that these DE-mRNAs were greatly enriched in some cancer-related GO items such as cell adhesion [39], cell-matrix adhesion [40], regulation of cell cycle and angiogenesis [41]. In addition, KEGG pathway enrichment analysis also proved that these significant DE-mRNAs had association with mTOR signaling pathway and p53 signaling pathway, which regulated the invasion and metastasis of cervical cancer [42,43]. These results suggested that DE-mRNAs identified through intersection of GEO datasets may play important roles in cervical cancer.…”
Section: Discussionmentioning
confidence: 92%